Pengaruh Brand Image dan E-Service Quality Terhadap Keputusan Pembelian Konsumen Melalui Marketplace Tokopedia (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis UNISMA 2018) - Muhammad Arif Muchtarom; Agus Widarko; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine and analyze the effect of Brand Image and E-Service Quality on consumer purchasing decisions through the Tokopedia marketplace. The population in this study were 2018 students of the Faculty of Economics and Business, Islamic University of Malang, who had made purchases on the Tokopedia marketplace. The data collection method in this study used a questionnaire with a sample of 75 respondents. The independent variable in this study is Brand Image with E-Service Quality and the dependent variable is Purchase Decision. The analytical method used in this study is multiple linear regression analysis and processed using SPSS 14. The results of this study simultaneously show that Brand Image and E-Service Quality have a positive and significant effect on purchasing decisions. Partially, Brand Image and E-Service Quality have a positive and significant effect on Purchase Decisions. Keywords: Brand Image, E-Service Quality, Keputusan Pembelian